THE ROLE AND PROSPECTS OF MAQOM MUSIC IN INTERNATIONAL CULTURAL PROJECTS - Masharipova Elmira Muxammedsharipovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the role of Maqom music in international cultural projects and examines its prospects for global promotion. The study focuses on how Maqom, as a representative of Uzbekistan’s musical heritage, can be integrated into cultural diplomacy, international festivals, and collaborative artistic initiatives. The paper explores strategies for enhancing the visibility of Maqom, engaging global audiences, and leveraging both traditional and digital platforms to ensure its sustainability and international recognition.